The Relevance of Hygiene to Health in Developing Countries - Potgieter, Natasha; Ndama Traore Hoffman, Afsatou (IntechOpen, 2019)
There are 17 comprehensive and detailed Sustainable Development Goals, which are all interlinked. Although access to water, sanitation, and hygiene is a human right, billions of people in developing countries are still faced with daily challenges accessing even the most basic of services, specifically the poor and vulnerable in communities. Hygiene is an important aspect for women/girls to access the economic, educational, and social opportunities they deserve. Proper hygiene removes disease as a barrier for equality, economic growth, and more. The role of hygiene in water, sanitation, and infections must be addressed from both scientific and social perspectives. This book provides the reader with an analysis of hygiene behaviors and practices and provides evidence-based examples in a number of developing countries.